Determinan Work Engagement dan Proactive Personality Terhadap Innovation Work Behaviour pada Karyawan Generasi Milenial di Jakarta - Lailla, Nor; Tarmizi, M. Irfan; Hananto, Djoko; Gunawan, Ade (Universitas Batanghari Jambi, 2024)
Innovative work behavior (IWB) is a very important factor in achieving competitive advantage and continuity of an organization, especially for millennial employees. This research discusses Work Engagement and Proactive Personality that occur in millennial generation employees. The method used in this research is a quantitative method with a population of millennial generation employees in Jakarta. The sample used used a sampling technique, namely purposive sampling, with 100 respondents. The results of this research are that the Work Engagement variable has a significance value for Innovation work behavior of 0.049, while the Proactive Personality variable has a significance value for Innovation work behavior of 0.058. From the coefficient of determination, it can be concluded that the Work Engagement and Proactive Personality variables influence Innovation work behavior by 16.6%, while the other variables are 83.4% influenced by other variables.